Betrachtungen zum japanischen Zensus von 1955 - Schwind, Martin (ERDKUNDE, 1957)
According to the 1955 census the population of Japan has reached 89.2 millions. Careful calculations make it likely that the 100 million mark will be reached in about 1970. Scarcity of land and mineral resources make family planning necessary. The statistical basis of the 1955 census differs greatly from that of all earlier ones; it is related to the new civil parishes created since 1953, which came into being by the incorporation of smaller administrative units into larger ones. This is shown in detail in the example of Ibaraki-Ken. Altogether there were in Japan in 1955 492 towns with over 30,000 inhabitants, and out of this number 98 were large cities of over 100,000. For the so-called Big Six, i. e. Tokyo, Yokohama, Osaka-Kobe, Nagoya and Kyoto, further administrative reforms will be necessary to facilitate proper planning for future development.